Efecto de la oxitocina sobre lipoperoxidación inducida por hiperalgesia en Rattus rattus var. Holtzman ovariectomizadas - Samillan Moya, Adriana (2017)
In the present investigation, the effect of oxytocin on lipoperoxidation induced by hyperalgesia in Rattus rattus var. Holtzman ovariectomized. Twenty-four ovariectomized female specimens were used between 2 and 4 months of age, with weights ranging from 200 to 250g, distributed randomly in 4 experimental groups; Control, problem 1, problem 2 and pattern. The control group received distilled water of 0.1mL / 100g, groups 1 and 2 were given oxytocin at a dose of 20IU/kg and 40IU/kg respectively, and finally the tramadol group received doses of 20mg /kg Intraperitoneal route; Followed by hyperalgesia by means of the Hot-plate, a model to evaluate antinociceptive effects against an acute thermal stimulus. The serum samples were extracted and the serum samples were used to determine the antioxidant effect according to levels of malondialdehyde using the colorimetric method of Thiobarbituric acid reactive substances (TBARS) read at 532 nm. It was concluded that oxytocin at doses of 20 and 40IU/kg had an antioxidant effect according to a decrease in the serum concentration of malondialdehyde (p≤0.05), with a higher antioxidant effect at doses of 20IU/kg with 0.1650mmol/mL of MDA in serum